Actions of N-arachidonyl-glycine in a rat inflammatory pain model - Vaughan Christopher W; Mitchell Vanessa A; Succar Rebecca (SAGE Publishing, 2007)
Abstract Background While cannabinoid receptor agonists have analgesic activity in inflammatory pain states they produce a range of side effects. Recently, it has been demonstrated that the arachidonic acid-amino acid conjugate, N-arachidonyl-glycine (NA-glycine) is effective in acute pain models. Results In the present study we examined the effect of NA-glycine in a rat model of inflammatory pain. Intrathecal administration of NA-glycine (70 - 700 nmol) and the pan-cannabinoid receptor agonist HU-210 (10 nmol) reduced the mechanical allodynia and thermal hyperalgesia induced by intraplantar injection of Freund's complete adjuvant (FCA). The actions of HU-210, but not NA-glycine were reduced by the cannabinoid CB1 receptor antagonist AM251. The cannabinoid CB2 receptor antagonist SR144528 also had no effect on the actions of NA-glycine. In contrast, N-arachidonyl-GABA (NA-GABA, 700 nmol) and N-arachidonyl-alanine (NA-alanine, 700 nmol) had no effect on allodynia and hyperalgesia. HU-210, but not NA-glycine produced a reduction in rotarod latency. Conclusion These findings suggest that NA-glycine may provide a novel non-cannabinoid receptor mediated approach to alleviate inflammatory pain.